2019
DOI: 10.2147/ott.s223702
|View full text |Cite
|
Sign up to set email alerts
|

<p>LOXL1-AS1 Drives The Progression Of Gastric Cancer Via Regulating miR-142-5p/PIK3CA Axis</p>

Abstract: BackgroundGastric cancer (GC) is a deadly disease, and its incidence is especially high in East Asia including China. Recently, some long non-coding RNA (lncRNAs) have been identified as oncogenes or tumor suppressors. This study aimed to determine the function and mechanism of lncRNA LOXL1-AS1 on the progression of GC.MethodsRT-PCR was done to measure the expression levels of LOXL1-AS1 and miR-142-5p in GC tissues. The association between pathological indexes and LOXL1-AS1 expression was also analyzed. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The present study indicated that FGd5-AS1 could function as a ceRNA to inhibit miR-142 expression. miR-142 has been identified to exert an inhibitory effect in several cancer types, including squamous cell carcinoma, gastric cancer and ovarian cancer (23)(24)(25). In addition, it has been demonstrated that miR-142 inhibits chemoresistance of various tumors, such as ovarian cancer and osteosarcoma (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicated that FGd5-AS1 could function as a ceRNA to inhibit miR-142 expression. miR-142 has been identified to exert an inhibitory effect in several cancer types, including squamous cell carcinoma, gastric cancer and ovarian cancer (23)(24)(25). In addition, it has been demonstrated that miR-142 inhibits chemoresistance of various tumors, such as ovarian cancer and osteosarcoma (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-375 inhibits the development of osteosarcoma via targeting PIK3CA [43]; In liver cancer, miR-124 impedes the proliferation of cancer cells via targeting PIK3CA [44]. It is reported that PIK3CA is a target of miR-142-5p in nonsmall cell lung cancer, gastric cancer, and pancreatic cancer [45][46][47]. In this work, it was demonstrated that miR-142-5p could negatively regulate PIK3CA mRNA and protein expressions in glioma cells.…”
Section: Discussionmentioning
confidence: 77%
“…LncRNA LOXL1-AS1 facilitates pancreatic cancer progression by promoting pancreatic cancer cell proliferation and migration ( 17 ). Moreover, LOXL1-AS1 facilitates gastric cancer progression by modulating the malignant phenotypes of gastric cancer cells ( 18 ) and facilitates the proliferation and invasion of non-small cell lung cancer cells ( 19 ). However, its role in liver cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%